An experience of mass administration of fractional dose inactivated polio vaccine through intradermal needle-free injectors in Karachi, Sindh, Pakistan - Umar Farooq Bullo; Jaishri Mehraj; Syed Musa Raza; Shumaila Rasool; Noreen Naz Ansari; Ahmed Ali Shaikh; Zamir Ali Phul; Sohail Ahmed Memon; Rehan Iqbal Baloch; Zahoor Ahmed Baloch; Shoukat Ali Chandio (BMC, 2021)
Abstract Background Inactivated Polio Vaccine (IPV) campaign was conducted in February 2019 in Karachi where needle-free injectors were introduced for the administration of the fractional dose of IPV (fIPV) on a large scale. This study aimed to determine the impact of needle-free injectors on vaccination coverage. Methods In four towns of Karachi, fIPV was given using needle-free injectors "PharmaJet Tropis ID". Whereas, in six towns full dose of IPV was administered to children of 4-59 months of age. Cluster surveys through rapid convenience assessment method were conducted after the completion of vaccination activity. Results A total of 33,815 households' data was analyzed. Among these, 27,650 (82.8%) children were vaccinated. In fIPV areas, 85.3% of children were vaccinated compared to 79.5% in full dose IPV areas. A comparison of reasons for unvaccinated showed that 1.6% of parents do not give importance to vaccination in fIPV areas compared to 4.2% in full IPV areas (p-value < 0.0001). More children were not vaccinated due to fear of injection 1.8% in full IPV areas compared to 0.7% in fIPV areas (p-value < 0.0001). The source of campaign information shows that more frequent mobile miking 3.1% was observed in fIPV areas compared to 0.4% in full IPV areas (p-value < 0.0001). Conclusions Our analysis supports the fractional dose of IPV in mass campaigns to achieve good vaccination coverage especially using needle-free injectors "PharmaJet Tropis ID" and vigorous social mobilization activities are expedient in accomplishing high coverage.